The Greedy Algorithm for the Symmetric TSP - Gutin, Gregory; Yeo, Anders (Algorithmic Operations Research, 2007)
We corrected proofs of two results on the greedy algorithm for the Symmetric TSP and answered a question in Gutin and Yeo, Oper. Res. Lett. 30 (2002), 97–99.